Perbandingan Efektivitas Dekolorisasi Fotokatalitik Metilen Biru dan Metil Jingga menggunakan Semikonduktor ZnO pada Variasi pH - Annisa M. Dewi; Wahyu B. Widayatno; Yuly Kusumawati (Universitas Andalas, 2019)
The comparison of photocatalytic decolorization of Methylene Blue and Methyl Orange using ZnO Semiconductor under UV-LED radiation has been studied at varied pH. ZnO have been synthesized using co-precipitation method. The Scanning Electron Microscopy (SEM) result showed that the synthesized ZnO has a hexagonal structure with the particle size range 0.125 to 0.5 Âµm. The BET isotherm characterization showed the synthesized ZnO has a specific surface area (SBET), mesoporous volume and micropore volume of 60.20 m2/g, 0.541 cm3/g and 0.02 cm3/g, respectively. The observation of the effect of pH to the photocatalytic activity showed that the highest removal percentage occurred at pH 9 with the value of 95.64% for methylene blue and occurred at pH 3 with the value of 6.236% for methyl orange.Â